Noninvasive Fluorine-19 Magnetic Resonance Relaxometry Measurement of the Partial Pressure of Oxygen in Acellular Perfluorochemical-loaded Alginate Microcapsules Implanted in the Peritoneal Cavity of Nonhuman Primates. Issue 2 (February 2020) - Safley, Susan A.; Graham, Melanie L.; Weegman, Bradley P.; Einstein, Samuel A.; Barber, Graham F.; Janecek, Jody J.; Mutch, Lucas A.; Singh, Amar; Ramachandran, Sabarinathan; Garwood, Michael; Sambanis, Athanassios; Papas, Klearchos K.; et al.
Abstract : Background: We have utilized a noninvasive technique for measuring the partial pressure of oxygen (pO2 ) in alginate microcapsules implanted intraperitoneally in healthy nonhuman primates (NHPs). Average pO2 is important for determining if a transplant site and capsules with certain passive diffusion characteristics can support the islet viability, metabolic activity, and dose necessary to reverse diabetes. Methods: Perfluoro-15-crown-5-ether alginate capsules were infused intraperitoneally into 3 healthy NHPs. Peritoneal pO2 levels were measured on days 0 and 7 using fluorine-19 magnetic resonance relaxometry and a fiber-optic probe. Fluorine-19 MRI was used to determine the locations of capsules within the peritoneal space on days 0 and 7. Gross and histologic evaluations of the capsules were used to assess their biocompatibility postmortem. Results: At day 0 immediately after infusion of capsules equilibrated to room air, capsules were concentrated near the infusion site, and the pO2 measurement using magnetic resonance relaxometry was 147 ± 9 mm Hg. On day 7 after capsules were dispersed throughout the peritoneal cavity, the pO2 level was 61 ± 11 mm Hg. Measurements using the fiber-optic oxygen sensor were 132 ± 7.5 mm Hg (day 0) and 89 ± 6.1 mm Hg (day 7). Perfluoro-15-crown-5-ether capsules retrieved on day 7 were intact and free-floating without host cell attachment, although the numbers of peritoneal CD20 + B cells, CD4 + and CD8 + T cells, and CD14 + macrophages increased consistent with a mild foreign body reaction. Conclusions: The peritoneal pO2 of normal NHPs is relatively low and we predict would decrease further when encapsulated islets are transplanted intraperitoneally.